Respuesta :
Answer:
1. [tex]x=-5[/tex]
2. [tex]x=7[/tex]
Step-by-step explanation:
First Equation
1. For the first equation, [tex]3x+10=-5[/tex] we need to move all the constants to one side.
[tex]3x+10=-5\\3x=-15[/tex]
2. Once that is done, we need to divide both sides by 3 to get [tex]x[/tex] by itself.
[tex]3x=-15\\\frac{3x}{3}=\frac{-15}{3}[/tex]
3. Now, we have our final answer.
[tex]x=-5[/tex]
Second Equation
1. For the second equation, [tex]3x-12=9[/tex] we need to move all the constants to one side.
[tex]3x-12=9\\3x=21[/tex]
2. Once that is done, we need to divide both sides by 3 to get [tex]x[/tex] by itself.
[tex]3x=21\\\frac{3x}{3} =\frac{21}{3}[/tex]
3. Now, we have our final answer.
[tex]x=7[/tex]
Hope this helped C: